Whole-genome sequencing-based genetic diversity, transmission dynamics, and drug-resistant mutations in Mycobacterium tuberculosis isolated from extrapulmonary tuberculosis patients in western Ethiopia - Chekesa, Basha; Singh, Harinder; Gonzalez-Juarbe, Norberto; Vashee, Sanjay; Wiscovitch-Russo, Rosana; Dupont, Christopher L.; Girma, Musse; Kerro, Oudessa; Gumi, Balako; Ameni, Gobena (Frontiers in Public Health, 2024)
Extrapulmonary tuberculosis (EPTB) refers to a form of Tuberculosis (TB) where the infection occurs outside the lungs. Despite EPTB being a devastating disease of public health concern, it is frequently overlooked as a public health problem. This study aimed to investigate genetic diversity, identify drug-resistance mutations, and trace ongoing transmission chains. A cross-sectional study was undertaken on individuals with EPTB Patients from August 5, 2018, to December 30, 2019, in western Ethiopia. In this study, whole-genome sequencing (WGS) was employed to analyze Mycobacterium tuberculosis (MTB) samples obtained from EPTB patients. Out of the 96 genomes initially sequenced, 89 met the required quality standards for genetic diversity, and drug-resistant mutations analysis. The data were processed using robust bioinformatics tools. Our analysis reveals that the majority (87.64%) of the isolates can be attributed to Lineage-4 (L4), with L4.6.3 and L4.2.2.2 emerging as the predominant sub-lineages, constituting 34.62% and 26.92%, respectively. The overall clustering rate and recent transmission index (RTI) were 30 and 17.24%, respectively. Notably, 7.87% of the isolates demonstrated resistance to at least one anti-TB drug, although multi-drug resistance (MDR) was observed in only 1.12% of the isolates. The genetic diversity of MTBC strains in western Ethiopia was found to have low inter-lineage diversity, with L4 predominating and exhibiting high intra-lineage diversity. The notably high clustering rate in the region implies a pressing need for enhanced TB infection control measures to effectively disrupt the transmission chain. It's noteworthy that 68.75% of resistance-conferring mutations went undetected by both GeneXpert MTB/RIF and the line probe assay (LPA) in western Ethiopia. The identification of resistance mutations undetected by both GeneXpert and LPA, along with the detection of mixed infections through WGS, emphasizes the value of adopting WGS as a high-resolution approach for TB diagnosis and molecular epidemiological surveillance.